PENGGUNAAN EKSTRAK FERMENTASI BERAS DARI BEBERAPA JENIS Monascus purpureus UNTUK AKTIVITAS INVITRO FAGOSITOSIS SEL MAKROFAG DAN POLIMORFONUKLEAR PERITONEUM MENCIT SEBAGAI IMMUNOMODULATOR [In Vitro Phagocytosic Activities of Macrophage and Polymorphonuclear Cell as Immunomodulator Effect of Rice Fermentation Extract by using Several Strains of Monascus purpureus] - Yulinery, T; Nurhidayat, N (Research Center for Biology-Indonesian Institute of Sciences, 2012)
Fermentation of rice by Monascus purpureus could produce red yeast rice (angkak) that can be used as drugs to decrease cholesterol and triglycerides increase thrombocyt in patients of dengue fever. To increase the immune system is needed the compounds that can be produced by microorganisms. The aim of study is to know that several strains of Monascus purpureus could produce the immunomodulatory effects or not. The study is about the invitro of phagocytosic activities of macrophage cell and polymorphonuclear of mice. This study had been used the fermented rice extract of five concentration such as 1 mg/ml, 0.1 mg/ml, 0.01 mg/ml, 0.001 mg/ml and 0.0001 mg/ml. As positive control was used 5 mg/ml extracts of meniran herbal, suspension of Staphylococcus aureus and the liquid of mice peritoneum. The results showed that the extract of fermented rice of Monascus purpureus with 1 mg/ml concentration was the same effectiveness as positive control. The conclusion was the extract of fermented rice could increase the fagocyticyt activities of can be concluded that administration of extract some kind of Monascus purpureus to increase the phagocytosis activities of macrophages and polymorphonuclear cells of mice.